Peran Kejaksaan Republik Indonesia dalam Penegakan Hukum terhadap Tindak Pidana Perdagangan Orang dan Tindak Pidana dalam Bidang Ketenagakerjaan - Dwight Nusawakan; Muhammad Khaidir Kahfi Natsir (Pusat Riset dan Inovasi Nasional, 2025)
Cases of criminal acts of trafficking in persons in certain cases are usually related to cases of criminal acts in the field of employment. To achieve legal certainty in law enforcement, especially for perpetrators of trafficking in persons and crimes in the field of employment, the principle of a legal state that has legislation as its rules is needed, law enforcement officers who are professional, have integrity and discipline, so that the law becomes a central thing in regulating and controlling the life of the nation and state. The crime of human trafficking is a general criminal case in which the prosecutor's handling process acts as a Public Prosecutor and other authorities are regulated by law. The prosecutor's office in the law enforcement process in Indonesia handles various types of criminal cases, one of which is the crime of human trafficking and employment crimes. This research aims to find out the role of the Republic of Indonesia Prosecutor's Office in Law Enforcement against Human Trafficking Crimes and Crimes in the Employment Sector. The approach method used in this research is normative juridical research (normative legal research method). The crime of trafficking in persons and the crime of employment have an interrelated modus operandi, where in this case there is an act of recruiting several people to serve as workers for a company, but these workers experience physical and psychological exploitation. In the Republic of Indonesia Prosecutor's Regulation Number 3 of 2024 concerning the Fourth Amendment to the Attorney General's Regulation Number PER-006/A/Ja/07/2017 concerning the Organization and Work Procedures of the Republic of Indonesia Prosecutor's Office contains the authority of the Prosecutor's Office in handling Human Trafficking and Employment Crime Cases.